Seasonal Vegetation Trends in Biomes of Türkiye: A Decade-Long Analysis Using NDVI Time Series - Aktürk, Emre (Bartin Orman Fakultesi Dergisi, 2024)
This study analyzes Türkiye's biomes' seasonal vegetation trend from 2014 to 2023 using the Normalized Difference Vegetation Index (NDVI) and Google Earth Engine (GEE). Focusing on Mediterranean Forests, Woodlands & Scrub; Temperate Broadleaf & Mixed Forests; Temperate Grasslands, Savannas & Shrublands; and Temperate Coniferous Forests biomes, it aims to illuminate vegetative trends and inform conservation strategies in line with the European Green Deal. Using Landsat 8 Operational Land Imager (OLI) satellite imagery and GEE's computational capabilities, the study efficiently processes large datasets, revealing distinctive vegetative responses to climatic conditions across biomes. Key findings include the resilience of Mediterranean vegetation to drought, stable growth in temperate broadleaf and mixed forests, dynamic seasonal shifts in grasslands, and consistent photosynthetic activity in coniferous forests. The study highlights the importance of continuous monitoring and suggests future research integrating remote sensing and ground observations for ecosystem management under climate change.
Keywords: 2. Zero hunger; 13. Climate action; 11. Sustainability; 15. Life on land